Engaging Citizens in Countries Affected by Fragility, Conflict, and Violence - Grandvoinnet, Helene (World Bank, Washington, DC, 2020)
This paper provides insights for World Bank staff to support a stronger understanding of the challenges, opportunities, and entry points to mainstreaming citizen engagement in fragility,conflict, and violence (FCV) contexts. It does not promise comprehensive solutions, rather a more nuanced view of citizen engagement in FCVs, and it suggests operational response. First, it summarizes what makes citizen engagement a necessary but challenging agenda. Second, it summarizes operational implications and suggestions for supporting citizen engagement using various FCV archetypes and examples of approaches to citizen engagement as a primer for the future direction of this agenda within the Governance Global Practice (GGP). The paper builds on the analysis conducted for the World Bank’s flagship report Opening the Black Box: The Contextual Drivers of Social Accountability, incorporating additional insights from the past few years. It is one in aseries of four papers from the GGP on citizen engagement in the areas of FCV situations, opengovernment, trust, and emerging technology.